Laparoscopic myomectomy instead of hysteroscopic myomectomy for large submucous fibroids - Chin-Jung Wang; Hsing-Tse Yu; Pei-Ju Wu; Hsuan Su; Kai-Yun Wu; Chien-Min Han (Wolters Kluwer Medknow Publications, 2013)
Objective: To evaluate the efficacy of laparoscopy in treating large submucous fibroids with deeply intramural invasion. Study design: Twenty-eight women with a main submucous fibroid >4 cm and with >50% intramural extension were enrolled in this study. Laparoscopic myomectomy was performed instead of hysteroscopic surgery. Results: Median fibroid diameter and weight were 5.0 cm [interquartile range (IQR) 4.6-6.0 cm] and 50.0 g (IQR 36.3-77.5 g), respectively. Median operating time was 60 minutes (IQR 50.0-73.8 minutes) and blood loss was 50 mL (IQR 50-100 mL). Median postoperative hospital stay was 2 days (IQR 2-3 days) and no patient developed complications. Seven women had coexistence of intramural and/or subserosal fibroids (median number of fibroids removed was 1, IQR 1-2). Conclusion: When the diagnosis of submucous fibroid >4 cm with >50% intramural extension is made, laparoscopic myomectomy can be performed instead of hysteroscopic surgery for the sake of safety and removal of nonsubmucous type fibroids concomitantly.